Potensi, Regulasi, dan Problematika Sertifikasi Halal Gratis - Nur Kasanah; Muhammad Husain As Sajjad (Journal of Economics, Law, and Humanities, 2022)
The research, which aims to determine the potential, regulations, and problems of the Free Halal Certification (Sehati) initiated by the Ministry of Religion through the Halal Product Guarantee Agency (BPJPH), is descriptive qualitative research that uses a phenomenological approach and a legal approach. The results show that the free halal certification program's potential success is supported by many micro and small business actors and the majority of the Indonesian Muslim population as a market. Free Halal Certification Regulations for Micro and Small Businesses are carried out using the halal self-declare with assistance from the Halal Product Process Facilitator (PPH) based on Law no. 33 of 2014, PP No. 39 of 2021, PMA No. 20 of 2021, Kepkaban No. 77 of 2021 and Kepkaban No. 33 of 2022. Problems that arise in the implementation of Sehati include: lack of socialization and information about the existence of the program, the role of stakeholders is not optimal, PPH assistants who are less thorough in verifying so that many files are returned, not yet business actors who are not responsive to Sehati regulations and digital services, the lack of maximum assistance in the process of halal products.